National campaign “bordeaux may” 2024 to raise awareness and combat headaches: event report - Oliveira, Daniella Araújo de; Andrade, Juliana; Cysneiros, Helena; Maciel, Taciana; Feitosa, Hugo; Candido, Poliana; Reis, Emanuel; Sampaio, Maria Clara; Severo, José Luiz; Almeida, Davi de; Neto , Ernandes de Souza; Ramos, Maria Vitória; et al. (Headache Medicine, 2024)
Introduction: The Global Burden of Disease 2021 study ranks headache disorders as the third leading cause of years lived with disability, however, they are still under-recognized, under-diagnosed and under-treated globally. The Brazilian Headache Society, through its "Bordeaux May " campaign, aims to raise awareness about headaches among the general population and health care professionals. Objective: To describe the sociodemographic profile and clinical characteristics of the headaches of those interviewed during the event. Methods: This is a cross-sectional study, conducted by the Federal University of Pernambuco in partnership with the Brazilian Headache Society. The event took place on May 19th, 2024, in the Jaqueira Park, Recife, and 157 volunteers were interviewed (60.9% women, 39.1% men). Data regarding age, sex, presence of headache, visits to the emergency room due to headache, medication administered in such visits and whether they were resolutive or not, as well as self-medication habits, proper health care access and its efficiency were collected. Results: Headaches were referred in 77.1% of the sample (n=121/157, 75 women, 45 men), and led to emergency room visits up to 3 times within the last year for 26 individuals (15 women, 5 men). The medications most administered on these occasions were analgesics, being resolutive in 69,2% of the patients. Self-medication was reported by 82.5% of the sample, while 78.3% are not undergoing any treatment for their condition. The main triggering factors were stress (62.5%), sleep deprivation (54.1%), and menstrual cycle (53.3% of the women). Conclusion: There was a high prevalence of headache in the sample, and women were more affected than men. Over half of the volunteers experiencing headaches did not seek medical help, likely leading to the high rate of self-medication observed. These findings highlight the urgent need to educate the population about headaches, as well as expanding access to proper health care.